Goal-driven attentional capture by appetitive and aversive smoking-related cues in nicotine-dependent smokers. (1st September 2018) - Brown, Chris R.H.; Forster, Sophie; Duka, Theodora
Highlights: Interference on target detection by irrelevant smoking distractors was tested. Irrelevant smoking distractors only interfered when matching the current search goal. Appetitive and aversive smoking distractors both showed goal matching interference. Smoking related distractors did not interfere with detecting a non-smoking target. Smoking distractor interference did not differ between smokers and non-smokers. Abstract: Background: Conventionally, involuntary attentional capture by tobacco cues in smokers are seen as an implicit bias, operating independently of current search goals. Prominent attention research, however, has suggested that search goals can induce an involuntary attentional capture. In the current investigation, we tested whether appetitive and aversive smoking images affected attention through such a mechanism and whether there were group differences based on nicotine dependence. Methods: We instructed non-smokers (NS), occasional smokers (OS; low dependence), and nicotine-dependent smokers (NDS; moderate-high dependence), to hold search goals for either an aversive or appetitive smoking category, or a category of non-smoking images. These images were presented in a stream of briefly appearing filler images, while task-irrelevant distractors were presented outside the stream. Distractors could be aversive or appetitive smoking images or a category of non-smoking images. Therefore, in some conditions, the distractors matched the current category being searched for, while in others it was incongruent. Results: Task-irrelevant smoking distractors reduced target detection, compared to the non-smoking distractors, only when they were congruent with the specific category being searched for. There was no effect of either aversive or appetitive smoking distractors on performance when participants were searching for the non-smoking targets. Distractor interference did not differ between smokers and non-smokers. Conclusions: The results support a goal-driven mechanism underpinning involuntary attentional capture by smoking cues. These findings can be used to inform models of addiction and attention, and the display of health warnings.